Curcumin targets YAP1 to enhance mitochondrial function and autophagy, protecting against UVB-induced photodamage - Chen, Quan; Lin, Wenxin; Tang, Yi; He, Fengmei; Liang, Bihua; Chen, Jiaoquan; Li, Huaping; Zhu, Huilan (Frontiers in Immunology, 2025)
BackgroundUltraviolet B (UVB) radiation is a major environmental factor contributing to skin damage via DNA damage, oxidative stress, inflammation, and collagen degradation. It penetrates the epidermis, disrupts DNA integrity, and generates reactive oxygen species (ROS), activating pro-inflammatory pathways such as NF-κB and AP-1, and inducing matrix metalloproteinases (MMPs). These processes lead to structural skin changes, inflammation, and pigmentation disorders like melasma. Cumulative DNA damage from UVB also drives photocarcinogenesis, with nearly 90% of melanomas associated with UV radiation (UVR). Despite clinical interventions like phototherapy and antioxidants, effective treatments for UVB-induced damage remain limited due to side effects and efficacy issues.MethodsThis study investigates the protective effects of curcumin on UVB-induced skin damage using a mouse UVB irradiation model and HaCaT cells exposed to UVB in vitro. Skin damage was assessed through histopathological and immunohistochemical analyses. Cellular functional changes were evaluated using assays for cell viability, mitochondrial function, ROS levels, and apoptosis. Transcriptomic analysis was employed to elucidate the molecular mechanisms underlying curcumin’s protective effects on HaCaT cells post-UVB exposure. This integrated approach provides a comprehensive understanding of curcumin’s molecular-level protection against UVB-induced skin damage.ResultsCurcumin significantly alleviated UVB-induced skin lesions and inflammation in vivo. In vitro, it mitigated UVB-induced HaCaT cell damage, enhancing viability while reducing apoptosis and ROS levels. Transcriptomic analysis revealed that curcumin upregulated YAP signaling and mitochondrial autophagy while suppressing IL-18 expression.ConclusionCurcumin treatment markedly improved UVB-induced skin lesions and reduced epidermal inflammation and thickness in vivo. In vitro, curcumin intervention alleviated UVB-induced HaCaT cell damage, including reduced viability, increased apoptosis, elevated ROS and DNA damage, and enhanced inflammatory responses. Transcriptomic analysis demonstrated that curcumin upregulated the YAP signaling pathway and mitochondrial autophagy while inhibiting the IL-18 pathway. Further studies revealed that curcumin directly interacts with YAP1, promoting mitochondrial autophagy, an effect blocked by the YAP1 inhibitor Verteporfin. Additionally, curcumin enhances mitochondrial function through YAP1, maintaining mitochondrial integrity and preventing the release of mitochondrial DNA (mtDNA) and mitochondrial ROS (mtROS), thereby suppressing NLRP3/IL-18 pathway activation.